Heterojunction‐assisted Co3S4@Co3O4 core – shell octahedrons for supercapacitors and both oxygen and carbon dioxide reduction reactions - Yan, Yibo (2020)
Expedition of electron transfer efficiency and optimization of surface reactant adsorption products desorption processes are two main challenges for developing non-noble catalysts in the oxygen reduction reaction (ORR) and CO2 reduction reaction (CRR). A heterojunction prototype on Co3 S4 @Co3 O4 core-shell octahedron structure is established via hydrothermal lattice anion exchange protocol to implement the electroreduction of oxygen and carbon dioxide with high performance. The synergistic bifunctional catalyst consists of p-type Co3 O4 core and n-type Co3 S4 shell, which afford high surface electron density along with high capacitance without sacrificing mechanical robustness. A four electron ORR process, identical to the Pt catalyzed ORR, is validated using the core-shell octahedron catalyst. The synergistic interaction between cobalt sulfide and cobalt oxide bicatalyst reduces the activation energy to convert CO2 into adsorbed intermediates and hereby enables CRR to run at a low overpotential, with formate as the highly selective main product at a high faraday efficiency of 85.3%. The remarkable performance can be ascribed to the synergistic coupling effect of the structured co-catalysts; heterojunction structure expedites the electron transfer efficiency and optimizes surface reactant adsorption product desorption processes, which also provide theoretical and pragmatic guideline for catalyst development and mechanism explorations.